ANALYSIS OF FACTORS CAUSING THE LOW SUBSCRIPTION LEVEL OF PDAM TIRTA SARI IN BINJAI CITY - Feby Melanie; Ruri Prihatini Lubis; Dasar Martinus Sembiring; Said Iqbal Zaini; Sahri Muda; Rudi Iskandar; Ade Farnan Saragih; Suangro L.H. Sitanggang (Bulletin of Engineering Science, Technology and Industry, 2025)
The low level of drinking water subscriptions at PDAM Tirta Sari in Binjai City is a problem that needs to be studied to determine the causal factors. This study aims to analyze the factors that most influence the low interest of the people of Binjai City in subscribing to PAM. The method used is a weighting and ranking analysis of several hypotheses related to tariffs, water quality, service continuity, network coverage, and the availability of alternative water sources. The results of the analysis indicate that the mismatch between PDAM Tirta Sari Binjai City's tariffs and the quality of services provided is the most dominant factor influencing the low level of subscriptions at PDAM Tirta Sari Binjai City. This factor is ranked first with the highest total value. Other factors that also influence are low water pressure, limited distribution network coverage, and the existence of alternative water sources, while the quality of PDAM Tirta Sari Binjai City's water sourced from the Bingai River Watershed (DAS) has the lowest influence compared to other factors.